Peramalan Kurs Rupiah Terhadap Dolar Amerika Menggunakan Jaringan Saraf Tiruan - Rifani Rizki Amelia; Fadhilah Fitri (Journal of Mathematics UNP, 2022)
The Indonesian rupiah (IDR) exchange rate is used to gauge Indonesia's economic stability. Maintaining the IDR exchange rate's stability is critical since it has a direct impact on Indonesia's national monetary situation, particularly during the Covid-19 pandemic. Forecasting is one way to assess government policy in terms of lowering the exchange rate. The goal of this study is to use the backpropagation artificial neural network model to model and predict the IDR exchange rate. This study uses daily data on the US Dollar (USD) to Indonesian Rupiah (IDR) exchange rate from March 2020 to December 2021. The best BPNN model is BP (2,5,1) with 2 neurons in the input layer, 5 neurons in the hidden layer, and 1 neuron in the output layer. The accuracy of prediction of this model is very good with an RMSE value is 33,66 and MAPE value is 0,1796%.